Three Paradoxes of the Future Prediction - D. V. Pivovarov (Russian State Vocational Pedagogical University, 2015)
The paper is devoted to the issue of predicting the future. While creating the future image of the mankind as a whole, and Russia in particular, extrapolated some 50 or 100 years ahead, such cultural forms as religion, philosophy, education and art make their significant impact. However, philosophy plays a special role of critical methodology in coordinating the futurological efforts. It works as a tuning fork that tunes up the orchestra of various sciences and other forms of social consciousness. Being dialectical, philosophers find out and analyze the contradictions - paradoxes, antinomies, and aporias - involved in such activities as prophesizing, prognosticating, predicting and foreseeing. On the basis of the retrospective analysis, the author considers the most significant paradoxes facing the futurologists engaged in predicting the general course of historic events; the paradoxes being denoted as follows: the antinomy of academic ignorance, paradox of newness and paradox of an emergent effect. The analysis results in conclusion that the large-scale, long-term «scientific predictions of the future», claiming to be the truth and pretending for historical value and accuracy, are impossible or at least doubtful. Nevertheless, global prognoses are highly valued, widely discussed and always in demand in society due to the purposeful human intellect.